PENENTUAN KOMPOSISI OPTIMUM BETON MARINE BERBASIS KONSEP REABILITAS - Armin Naibaho (Prokons: Jurnal Teknik Sipil, 2017)
The terminology ’marine concrete’ resrved for concrete material to structures in the marine area extreme condition. Many civil engineering building in the suburban sea area, for example dock and retaining scouring waves wall. Be expected of this fly ash utilization of waste can answer market (construction world) request to readymix concrete request with price which more economial but with quality which stay awake. This observation purpose to: (1) determining the optimum composition to concrete in the moring area (with extreme condition) with involves these aspecks as “high performance concrete “ that is : high strength, high fracture resistance, low permeability, shrinkage controlled creep,(2). Study of interface zone condition with involves aspects of cohesion to determine Mode I Fracture Resistance.Based on the results of analysis and discussion, so we have: (1). Show that the used of the number fly ash 10% will produce the greatest compressive strength-caracteristik  =  58,56 MPa, whereas without the used of fly ash ( 0 %) obtained  =  56,44 MPa, (2). Calculation of probability and reability obtained values: to tested specimen which do not use fly ash (0%; Reliability is ↔ R = 1 – P  = 1 – 0,72 = 0,28 and the addition of 10% fly ash, obtained Reliability is ↔ R = 1 – P  = 1 – 0,70 = 0,30.Suggested the need for the selection of quality materials, procedures In the implemention and maintenance of  the test specimen after casted suggested thats need tight control to produce compressive strength field in maximum.  Keywords : marine concrete, fly ash, compressive strength, mixture variatio, probability and reability.